Meta-Analysis The Effect of Maternal Obesity on the Risk of Premature Birth and Neonatal Death - Wulandari, Fitria; Budihastuti, Uki Retno; Pamungkasari, Eti Poncorini (Journal of Maternal and Child Health, 2021)
Background: The prevalence of obesity in women of reproductive age worldwide is increasing by an estimated 20-36%. Increased prevalence of obesity also occurs in pregnant women. Obesity increases the risk of poor pregnancy outcome. This study aims to investigate the effect of maternal obesity on preterm birth and neonatal mortality. Subjects and Method: This was a systematic review and meta-analysis. The articles used were obtained from several databases, including: Google Scholar, Science Direct, Springer Link, Proquest, and Scopus published from 2010 to 2021. The population in this study was pregnant women with an intervention in the form of obesity, comparison in the form of normal BMI, and outcome such as premature birth and neonatal death. The keywords used to search for articles were: (“maternal obesity” OR “maternal BMI”) AND (“premature birth” OR “preterm birth” OR “preterm delivery” OR “preterm labor”) AND (“neonatal mortality” OR “ neonatal death”) AND “adjusted Odds Ratio”, and “maternal obesity” AND (“premature birth” OR “preterm birth” OR “preterm delivery”) AND (“neonatal mortality” OR “neonatal death”) AND “adjusted Odds Ratio ". The article is a full text article with a cross-sectional and cohort study design. Articles were collected using PRISMA flow diagrams and analyzed using the Review Manager 5.3 . application. Results:  There were 19 articles reviewed in the study. A meta-analysis of 13 cohort studies showed that obese pregnant women were 1.02 times more likely to have a premature birth when compared to normal BMI pregnant women, but this result was not statistically significant (aOR=1.02; 95% CI=0.93 to 1.13; p=0.630). A meta-analysis of 4 cohort studies showed that maternal obesity increased the risk of neonatal death and was statistically significant (aOR=1.52; 95% CI=1.17 to 1.99; p=0.002). A meta-analysis of 4 cross-sectional studies showed that maternal obesity increased the risk of neonatal death and was statistically significant (aOR=1.44; 95% CI=1.26 to 1.64; p<0.001). Conclusion:  Maternal obesity increases the risk of neonatal death which is statistically significant and the risk of preterm birth which is not statistically significant.